Immune checkpoint inhibitors: a new landscape for extensive stage small cell lung cancer treatment. (2nd November 2021) - Bianco, Andrea; D'Agnano, Vito; Matera, Maria Gabriella; Della Gravara, Luigi; Perrotta, Fabio; Rocco, Danilo
ABSTRACT: Introduction : Landscape of Extensive Stage (ES)-SCLC treatment has been unchanged over the years. Chemotherapy, mostly based on cisplatin and etoposide, remained the standard-of-care for patients with ES-SCLC for almost 40 years. Recently, immune check points inhibitors have emerged marking a turning point for ES-SCLC treatment Areas covered : Aim of the paper is to discuss ICIs impact on ES-SCLC treatment algorithms, review current clinical trials, and explore future perspectives. Expert opinion : A growing body of evidence supports ICI-containing regimens as a new mainstay of ES-SCLC treatment. Whether subgroups of SCLC patients may have greater survival benefits from ICIs treatment needs to be better defined. Understanding the impact of tumor microenvironment and identifying reliable predictive and/or prognostic biomarkers will be fundamental to move toward a personalized treatment approach leading to improved survival.